British imperialism in Cyprus, 1878-1915 the inconsequential possession - Varnava, Andrekos 1979- (Manchester University Press, 2015)
This book explores how the Union Jack came to fly over the island of Cyprus and why after thirty-five years the British wanted it lowered. Cyprus’ importance was always more imagined than real and was enmeshed within widely held cultural signifiers and myths
Keywords: Geschichte 1878-1915; Colonialism & Imperialism / European history / bicssc; HISTORY / Europe / Great Britain / bisach; Colonialism & imperialism / European history / United Kingdom, Great Britain / thema; Cyprus / Foreign realtions / Great Britain; Cyprus / History / 19th century; Cyprus / History / 20th century; Great Britain / Foreign relations / Cyprus; Zypern; Großbritannien